Insertional translocation involving an additional nonchromothriptic chromosome in constitutional chromothripsis: Rule or exception?. Issue 2 (18th December 2018) - Kurtas, Nehir Edibe; Xumerle, Luciano; Giussani, Ursula; Pansa, Alessandra; Cardarelli, Laura; Bertini, Veronica; Valetto, Angelo; Liehr, Thomas; Clara Bonaglia, Maria; Errichiello, Edoardo; Delledonne, Massimo; Zuffardi, Orsetta
Abstract: Background: Chromothripsis, which is the local massive shattering of one or more chromosomes and their reassembly in a disordered array with frequent loss of some fragments, has been mainly reported in association with abnormal phenotypes. We report three unrelated healthy persons, two of which parenting a child with some degree of intellectual disability, carrying a chromothripsis involving respectively one, two, and three chromosomes, which was detected only after whole‐genome sequencing. Unexpectedly, in all three cases a fragment from one of the chromothripsed chromosomes resulted to be inserted within a nonchromothripsed one. Methods: Conventional cytogenetic techniques, paired‐end whole‐genome sequencing, polymerase chain reaction, and Sanger sequencing were used to characterize complex rearrangements, copy‐number variations, and breakpoint sequences in all three families. Results: In two families, one parent was carrier of a balanced chromothripsis causing in the index case a deletion and a noncontiguous duplication at 3q in case 1, and a t(6;14) translocation associated with interstitial 14q deletion in case 2. In the third family, an unbalanced chromothripsis involving chromosomes 6, 7, and 15 was inherited to the proband by the mosaic parent. In all three parents, the chromothripsis was concurrent with an insertional translocation of a portion of one of the chromothriptic chromosomes within a further chromosome that was not involved in the chromothripsis event. Conclusion: Our findings show that (a) both simple and complex unbalanced rearrangements may result by the recombination of a cryptic parental balanced chromothripsis and that (b) insertional translocations are the spy of more complex rearrangements and not simply a three‐breakpoint event. Abstract : We detected, by paired‐end whole‐genome sequencing, constitutional chromothripsis in all three unrelated healthy parents having affected (in two cases) and unaffected probands (in one case). The detailed characterization of chromothripsis in all three parents revealed an unexpected genomic "behavior" of chromothriptic fragments and repair mechanisms, showing that some of the fragments may escape the reconstitution of the new chromosome and instead be adopted by a nonchromothriptic chromosome, creating an insertional translocation.